DISCOURSE ANALYSIS IN CONSECUTIVE INTERPRETING - NECESSITY RATHER THAN AID - Jasmina P. Đorđević (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2012)
Translation in general and consecutive interpreting in particular, are both a process and a product dependent upon the language competence of the translator in at least two language systems, obviously based on the translatorʼs comprehensive knowledge of words, phrases and sentences in the two languages. The aim of this article is not to argue or support this claim, but rather to emphasise the necessity that the consecutive interpreter extend the said language competence and acquire the skill of linguistic analysis beyond the level of words, phrases and sentences - the domain of text and discourse. Already established in general linguistics as essential, text and discourse are related to translation and to consecutive interpreting as well. Recognition of pragmatically coherent patterns used in language and speech and their proper analysis may enable anticipation of yet new patterns and thus help the consecutive interpreter render the translated discourse faster, more coherently and more accurately. Hence the purpose of this article: to emphasise the importance of training interpreters to apply discourse analysis in the area of consecutive interpreting by illustrating some key translator training techniques to facilitate the skill. Although the implementation of these strategies would be much more effective if integrated into a methodologically structured course, they can be used as individual exercises for practice purposes as well.